2021
DOI: 10.1002/jcb.30131
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a novel methylation‐related prognostic model for colorectal cancer based on microsatellite status

Abstract: The present study aimed to construct a novel methylation‐related prognostic model based on microsatellite status that may enhance the prognosis of colorectal cancer (CRC) from methylation and microsatellite status perspective. DNA methylation and mRNA expression data with clinical information were downloaded from The Cancer Genome Atlas (TCGA) data set. The samples were divided into microsatellite stability and microsatellite instability group, and CIBERSORT was used to assess the immune cell infiltration char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Good calibrations were observed in the 1-year, 3-year, and 5-year predicted vs. observed survival rates ( Figure 6B ). The RMS of the TRPC nomogram was higher than that of the TRPC score and published models of Yang ( 32 ), Liu ( 33 ), and Cao ( 34 ) (P< 0.05, Figure 6C ). The C-index of the TRPC nomogram was 0.779, which was higher than that of the TRPC score and published models of Yang ( 32 ), Liu ( 33 ), and Cao ( 34 ) ( Figure 6D ).…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…Good calibrations were observed in the 1-year, 3-year, and 5-year predicted vs. observed survival rates ( Figure 6B ). The RMS of the TRPC nomogram was higher than that of the TRPC score and published models of Yang ( 32 ), Liu ( 33 ), and Cao ( 34 ) (P< 0.05, Figure 6C ). The C-index of the TRPC nomogram was 0.779, which was higher than that of the TRPC score and published models of Yang ( 32 ), Liu ( 33 ), and Cao ( 34 ) ( Figure 6D ).…”
Section: Resultsmentioning
confidence: 75%
“…The RMS of the TRPC nomogram was higher than that of the TRPC score and published models of Yang ( 32 ), Liu ( 33 ), and Cao ( 34 ) (P< 0.05, Figure 6C ). The C-index of the TRPC nomogram was 0.779, which was higher than that of the TRPC score and published models of Yang ( 32 ), Liu ( 33 ), and Cao ( 34 ) ( Figure 6D ). ROC curves revealed that the TRPC nomogram predicted the 1-year, 3-year, and 5-year OS more efficiently than the TRPC score and published models of Yang ( 32 ), Liu ( 33 ), and Cao ( 34 ) ( Figures 6E–G ).…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Extensive studies have been conducted to identify novel diagnosis, prognosis, and therapeutic targets for colon cancer [14][15][16][17]. However, more effective signatures needed to be explored.…”
Section: Discussionmentioning
confidence: 99%